IPP PROGRAM EVALUATION MODEL OF TEACHER SUPERVISION AT SDN 35 TALANG KELAPA, BANYUASIN REGENCY - Elfarissyah, Andria Mella; Suseno, Muchlas; Setiadi, Syamsi (English Community Journal, 2022)
The objective of this study was to evaluate the teacher supervision program based on the CIPP model that consists of context, input, process and product at SDN 35 Talang Kelapa, Banyuasin regency. Determining the effectiveness of the program supervision evaluation process is seen from the level of achievement of the program evaluation objectives that have been determined by the school. This research was a qualitative study that used the CIPP model by evaluating each component: context, input, process and product to achieve an effective supervision program evaluation process. Sources of research data are teachers at SDN 35 Talang Kelapa, Banyuasin Regency. Collecting the research data by using instruments, those were interview and questionnaire. From the results of the study, it showed that the implementation of the teacher supervision program based on the CIPP model (context, input, process and product) was declared that good and effective.